Beneficial effects of beta‐blockers on left ventricular function and cellular energy reserve in patients with heart failure. (9th February 2012) - Spoladore, Roberto; Fragasso, Gabriele; Perseghin, Gianluca; De Cobelli, Francesco; Esposito, Antonio; Maranta, Francesco; Calori, Giliola; Locatelli, Massimo; Lattuada, Guido; Scifo, Paola; Del Maschio, Alessandro; Margonato, Alberto
Abstract Beta‐blockers have been shown to improve left ventricular (LV) function in patients with heart failure. The aim of this study is to non‐invasively assess, by means of in vivo 31P‐magnetic resonance spectroscopy (31P‐MRS), the effects of beta‐blockers on LV cardiac phosphocreatine and adenosine triphosphate (PCr/ATP) ratio in patients with heart failure. Ten heart failure patients on full medical therapy were beta‐blocked by either carvedilol or bisoprolol. Before and after 3 months of treatment, exercise testing, 2D echocardiography, MRS, New York Heart Association (NYHA) class, ejection fraction (EF), maximal rate–pressure product and exercise metabolic equivalent system (METS) were evaluated. Relative concentrations of PCr and ATP were determined by cardiac 31P‐MRS. After beta‐blockade, NYHA class decreased (from 2.2 ± 0.54 to 1.9 ± 0.52, P = 0.05), whereas EF (from 33 ± 7 to 44 ± 6%, P = 0.0009) and METS (from 6.74 ± 2.12 to 8.03 ± 2.39, P = 0.01) increased. Accordingly, the mean cardiac PCr/ATP ratio increased by 33% (from 1.48 ± 0.22 to 1.81 ± 0.48, P = 0.03). Beta‐blockade‐induced symptomatic and functional improvement in patients with heart failure is associated to increased PCr/ATP ratio, indicating preservation of myocardial high‐energy phosphate levels.